The refuge effect of humid microhabitats for ferns decreases towards more arid regions - Páez, Saúl; Aros–Mualin, Daniela; Kessler, Michael; Kluge, Jürgen; Ismael Meza-Torres, Esteban (Frontiers in Ecology and Evolution, 2026)
Climate change is expected to intensify biodiversity loss through increasing aridity, but the potential of humid microhabitats to buffer these effects in tropical lowlands remains poorly understood. To address this gap, we surveyed 326 plots across 14 localities along a natural humidity gradient in northeastern Argentina, comparing fern diversity between climatically driven zonal habitats and more humid topographically or edaphically influenced azonal habitats. We found that azonal habitats supported greater fern richness than zonal ones in humid to semihumid regions, but this advantage disappeared towards the arid extreme, where both habitat types hosted equally poor communities. At the species level, only Christella hispidula and Doryopteris pentagona showed higher frequency patterns in azonal habitats toward drier conditions, whereas most species were more frequent in zonal habitats or showed no clear shift. Annual precipitation best explained variation in species richness, and soil conditions, such as salinity or unsuitable textures, may limit the capacity of azonal habitats to act as refugia under dry climates. Our findings reveal that humid microhabitats can act as refugia for ferns only under favorable moisture conditions, highlighting the need to account for local environmental heterogeneity and edaphic limitations when predicting biodiversity persistence under climate change.